Dear Black girls : how to be true to you - Wilson, A'ja, 1996- (Moment of Life Books, Flatiron Books, 2024)
"From Olympic gold medalist and two-time professional basketball MVP A'ja Wilson comes an inspirational collection on what it means to grow up as a Black girl in America. This is a book for all the girls with an apostrophe in their name. This is for all the girls who are "too loud" and "too emotional." This is for all the girls who are constantly asked, "Oh, what did you do with your hair? That's new." This is for my Black girls. In this empowering and deeply personal collection-adapted from and expanded upon the piece of the same name in The Players' Tribune-WNBA star A'ja Wilson shares stories from her life. Despite gold medals, championships, and a list of accolades, Wilson knows how it feels to be swept under the rug. To not be heard, to not feel seen, to not be taken seriously. As a fourth grader going to a primarily white school in South Carolina, she was told she'd have to stay outside for a classmate's birthday party. "Huh?" she asked. Because the birthday girl's father didn't like Black people. Wilson tells stories like this: stories that held her down but didn't stop her. She shares her contribution to "The Talk," and how to keep fighting, all while igniting strength, resilience, and passion. Dear Black Girls is one remarkable author's necessary and meaningful exploration of what it means to be a Black woman in America today-and an of-the-moment rally cry to lift up women and girls everywhere"--